Considerações sobre literatura e institucionalidade - DUARTE, Rafael Soares (Universidade Federal do Pará, 2019)
The purpose of this essay is to think about Literature as an object of study, what is the literature taught at school, and what can be taught to the student of literature, checking out the disparity and incongruence historically kept between the potentiality of Literature as a builder of the students intellectuality and the historicist direction presented at the regular study. Also are presented a few sketches of possible directions about the Literature teaching.